Penerapan Community Based Tourism Dalam Pengelolaan Pariwisata Pada Kelecung Eco Village, Desa Tegal Mengkeb, Kecamatan Selemadeg Timur, Kabupaten Tabanan - Wulandari, Ni Luh Nyoman Sri; Yasintha, Putu Nomy; Wijaya, Komang Adi Sastra (CITIZEN CHARTER, 2023)
Kelecung Eco Village is one of the sub villages in the Tegal Mengkeb Tourism Village which is currently developing its tourism potential. The management and development of tourism in Kelecung is community based which is often referred to as Community Based Tourism (CBT). This study aims to analyze tourism management at Kelecung Eco Village through the concept of Community Based Tourism (CBT). Community Based Tourism is a concept that involves community participation in managing the potential that exists in their area so that not only active participation but the community will get a real economic and social impact for the development and growth of their welfare. This research uses descriptive qualitative method. Data was collected by observation, interview and documentation methods. Analysis of the findings uses the theory of Tourism Development with a Community Based Tourism (CBT) approach according to Suansri (2003) in Sri Endah Nurhidayati through 5 (five) dimensions, namely: the economic dimension, the social dimension, the cultural dimension, the environmental dimension, and the political dimension. The findings show that from an economic dimension it has been going well, but the financial records do not use modern technology. Furthermore, for the social dimension, the findings show that this concept has worked well in terms of increasing community pride and also fair distribution of roles. Then for the cultural dimension it has been going well. For the environmental dimension, it has been going well, but the management of waste transportation does not use modern technology. Then the last one for the political dimension has been going well, but there is a lack of regulations governing tourism management arrangements at Kelecung Eco Village. As for the recommendations that the author can give, namely POKDARWIS Dewi Kesari which is produced using more modern technology in its management, POKDARWIS Dewi Kesari which makes general rules for tourists even if they only come on vacation but don't stay overnight, POKDARWIS Dewi Kesari is to make more activities to attract local people so that participation is increasing and the Tegal Mengkeb official village makes written rules for the management of the Kelecung Eco Village